Esketamine opioid-free intravenous anesthesia versus opioid intravenous anesthesia in spontaneous ventilation video-assisted thoracic surgery: a randomized controlled trial - Fan, Qisen; Luo, Jinhui; Zhou, Qianling; Zhang, Yaoliang; Zhang, Xin; Li, Jiayang; Jiang, Long; Lan, Lan (Frontiers in Oncology, 2023)
Background Opioid-free anesthesia (OFA) provides adequate analgesia and can reduce postoperative opioid consumption, but its efficacy in spontaneous ventilation video-assisted thoracic surgery (SV-VATS) has not been demonstrated. We aimed to investigate the hypothesis that OFA could provide the same perioperative pain control as opioid anesthesia (OA), maintain safe and stable respiration and hemodynamics during surgery, and improve postoperative recovery. Methods Sixty eligible patients (OFA group: n=30; OA group: n=30) treated between September 15, 2022, and December 15, 2022, at The First Hospital of Guangzhou Medical University were included. They were randomized to receive standard balanced OFA with esketamine or OA with remifentanil combined with sufentanil. The primary outcome was the pain numeric rating score (NRS) at postoperative 24 h, and the secondary outcomes were intraoperative respiratory and hemodynamic data, opioid consumption, vasoactive drug dosage, and recovery in the post-anesthesia care unit and ward. Results There was no significant difference in the postoperative pain scores and recovery quality between the two groups. The OFA group had a significantly lower dose of phenylephrine (P=0.001) and a lower incidence of hypotension (P=0.004) during surgery. The OFA group resumed spontaneous respiration faster (P<0.001) and had a higher quality of lung collapse (P=0.02). However, the total doses of propofol and dexmetomidine were higher (P=0.03 and P=0.02), and the time to consciousness was longer (P=0.039) in the OFA group. Conclusions OFA provides the same level of postoperative pain control as OA, but it is more advantageous in maintaining circulatory and respiratory stability and improving the quality of pulmonary collapse in SV-VATS.